MEDIA EDUCATIONAL TECHNOLOGIES IN THE FORMATION OF SENIOR SCHOOL STUDENTS’ LIFE SUCCESSFULNESS - Puhach, Anzhelina (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The article examines the peculiarities of the formation of life successfulness of senior school students based on the latest technologies in the modern conditions of the digital society. The author focuses on success and successfulness as fundamental values of the state and individual. The importance of critical thinking skills, flexibility and creativity, the ability to solve problems successfully for the effective and productive life of a growing personality is indicated. In this regard, attention is drawn to implementing media education and media educational technologies into school practice, as well as creating a constructive media educational environment. In the context of a multidimensional interdisciplinary discourse, an objective and subjective dimension of understanding the concepts of “life success” and “life successfulness” was revealed, which relates to the social recognition of a person and one’s assessment of one’s own actions as successful. Taking into account the ideas of researchers, we consider life successfulness as a personal quality associated with the realization of a life project, awareness of personal self-realization, subjective experience of one’s own success in various spheres of life based on relevant experience and everyday life practices with a sense of the meaning of life. The vision of educational technologies is clarified, including media educational technologies as a part of didactics and the learning process, during which educational tasks are implemented to form a successful media literate, media-aware personality of a teenager. The mission, principles and model of the school media hub as a media educational technology based on pedagogy of partnership and aimed at forming a life-successful personality of a high school student by mastering skills and abilities of effective and safe interaction with the mass media, informed understanding, creative elaboration and active dissemination of content, in particular patriotic content, nation-building content, protection against fakes, hostile propaganda, establishment of friendly communication in social networks for effective life activities in rapidly changing realities are represented. The correspondence of the presented generalizations to the ideas of foreign scholars regarding the connection between personal traits and success indicators, the importance of media literacy for everyday life, media culture in forming key competencies for preparing a child for life self-realization is substantiated.